2020
DOI: 10.1101/2020.08.11.246363
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Whole genome CRISPR screens identify a LRRK2-regulated pathway for extracellular tau uptake by human neurons

Abstract: Pathological protein aggregation in Alzheimer's disease and other dementias is proposed to spread through the nervous system by a process of intercellular transfer of pathogenic forms of tau protein. Defining the cellular mechanisms of tau entry to human neurons is essential for understanding dementia pathogenesis and the rational design of disease-modifying therapeutics. Using whole genome CRISPR knockout screens in human iPSC-derived excitatory neurons, the primary cell type affected in these diseases, we id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 79 publications
0
13
0
Order By: Relevance
“…This article is protected by copyright. All rights reserved has in the uptake of vesicle-free tau, and also in receptor recycling that when disrupted could likely have considerable impact on surface receptor numbers and composition at the plasma membrane [66].…”
Section: Accepted Articlementioning
confidence: 99%
“…This article is protected by copyright. All rights reserved has in the uptake of vesicle-free tau, and also in receptor recycling that when disrupted could likely have considerable impact on surface receptor numbers and composition at the plasma membrane [66].…”
Section: Accepted Articlementioning
confidence: 99%
“…Once in the extracellular space, pathological tau proteins need to be internalized into a neighboring recipient cell. This can also occur in several ways, including dynamin-dependent bulk endocytosis [ 67 ], macropinocytosis following heparan sulphate proteoglycan binding on the plasma membrane [ 68 , 69 ], and/or through the interaction with several specific receptors located at the cell surface, such as low-density lipoprotein receptor-related protein 1 (LRP1) [ 70 , 71 , 72 , 73 ]. Tau aggregates then leak into the cytosol by rupturing the endosomal membrane, where they can interact with physiological tau [ 74 , 75 ].…”
Section: Tau Protein Properties In Health and Diseasementioning
confidence: 99%
“…Neuronal tau uptake can occur through receptor-mediated endocytosis, for instance via heparan sulfate proteoglycans in conjunction with specific receptors like LRP1 [ 68 , 73 ]. Loss of function of the endocytosis regulator leucine-rich repeat kinase 2 ( LRRK2 ) is known to impede tau internalization by neuronal cells [ 70 ]. A recent study identified LRRK2-regulated receptor-mediated endocytosis as the main uptake mechanism for monomeric and aggregated tau species upon application of whole-genome clustered regularly interspaced short palindromic repeats (CRISPR) knockout screens in human induced pluripotent stem cell (iPSC)-derived excitatory neurons [ 70 ].…”
Section: Applications Of Patient-derived Tau Seeding Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…We next tested whether entry could be inhibited by reducing uptake to the cell. Previous studies have shown that tau uptake occurs via endocytosis and relies on the vesicle coat protein clathrin, as well as the GTPase dynamin (Calafate et al, 2016;Evans et al, 2018Evans et al, , 2020Shrivastava et al, 2019). We pre-treated cells with the clathrin inhibitor PitStop 2 or the dynamin inhibitor Dyngo 4a.…”
Section: Tau-hibit Assemblies Enter Cell Lines Via Clathrin-mediated Endocytosismentioning
confidence: 99%